Legal Comments on Employment Regulations for Enhancing Technology Transfer in Vietnam - Le Thu, Nguyen (VNU Journal of Science: Legal Studies; Vol 39 No 1, 2023)
Technology transfer is considered one of the main factors for innovation and enhancing productivity, then becomes a crucial policy in developing countries, including Vietnam. However, research has shown that innovation in Vietnam is under the expectation, especially at the enterprise level. One reason for this concern is the need for a stable supply of skilled employees to absorb, implement and re-distribute knowledge. Thus, this paper examines the issue from the perspective of employment law which mainly relates to the rights and obligations of employees and employers for the purpose of finding how these regulations might be supplemented to promote technology transfer. Legal recommendations are the primary outcomes of the paper.